2018
DOI: 10.1097/med.0000000000000382
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine manifestations of Down syndrome

Abstract: Recent research confirms and expands on the previously known endocrinopathies in Down syndrome and provides more insight into potential underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 49 publications
3
50
0
2
Order By: Relevance
“…Studies have linked the collapse of hair follicle immune privilege with dysregulation of T helper type 1 (TH1) cells, specifically CD8 + T cells, and subsequent increased expression of IFN‐γ 28 . The AIRE gene, which regulates self‐recognition and T‐cell function, has been implicated in AA immune dysregulation 29 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have linked the collapse of hair follicle immune privilege with dysregulation of T helper type 1 (TH1) cells, specifically CD8 + T cells, and subsequent increased expression of IFN‐γ 28 . The AIRE gene, which regulates self‐recognition and T‐cell function, has been implicated in AA immune dysregulation 29 …”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that pregnant women with a DS fetus suffer from lipid disorders related to disturbed cholesterol metabolism and lipid transport; incorrect distribution of VLDL, LDL, and lipid peroxidation [ 4 ]; and altered concentration of sphingolipids, which leads to improper myelination of fetal neurons [ 24 ]. These patients also show insufficient endothelial function, which is related to the inflammation process, oxidative stress, and dysregulated lipid metabolism, which may result in insufficient cell division [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…32 • Los pacientes con síndrome de Down presentan mayor riesgo de enfermedad tiroidea autoinmune (TLC y EG), de hipotiroidismo subclínico o hipertirotropinemia y de hipotiroidismo congénito. 16,33 Debido a esto, 10 mU/l deberían ser repetidos antes de iniciar el tratamiento, pues, en el 70 % de los casos, serán normales en la siguiente determinación. 24 Las alteraciones del sueño, el estrés y el calor 13 pueden modificar los valores de TSH.…”
Section: Diagnósticounclassified